A Method for the evaluation of knowledge management systems - Claudio Henrique dos Santos Grecco; Silas Cordeiro Augusto; Jaqueline Tavares Viana de Souza; Paulo Victor Rodrigues Carvalho; Adriana Loureiro Davila (Brazilian Journal of Radiation Sciences)
The explicit and tacit knowledge of workers constitute as valuable resources, as they enable organizations to perform their functions successfully. Such knowledge is derived from the qualification and experience of workers. On the other side, there are factors that favor the loss of this knowledge in organizations, as for example, the natural aging of workers and consequently the retirement and staff turnover. Because of these reasons, it becomes important for any organization to seek the preservation of its explicit and tacit knowledge. The Knowledge Management seeks to assist in the tasks of identification, organization, preservation and transmission of such knowledge. At the Nuclear Engineering Institute, three systems were developed and implemented to help in the Knowledge Management area: CarpeDIEN, a repository of research data based on the DSpace software; the “Nuclear Energy in Magazines”, a peer-reviewed academic journals management system based on the Open Journal Systems software; and WikiIEN, a wiki based on the MediaWiki software. Each of these systems presents a different proposal and workflow. The objective of this paper is to present the characteristics of each system, a method to compare them based on criteria presented in the literature and to point their weaknesses. The results showed that the method is a proactive tool to provide a basis for choosing the most appropriate system for a given need in an organization.